Combating Complement's Deleterious Effects on Nanomedicine by Conjugating Complement Regulatory Proteins to Nanoparticles (Adv. Mater. 8/2022). Issue 8 (24th February 2022) - Wang, Zhicheng; Hood, Elizabeth D.; Nong, Jia; Ding, Jing; Marcos‐Contreras, Oscar A.; Glassman, Patrick M.; Rubey, Kathryn M.; Zaleski, Michael; Espy, Carolann L.; Gullipali, Damodara; Miwa, Takashi; Muzykantov, Vladimir R.; et al.
Abstract : Nanomedicine Immediately upon encountering blood, nanoparticles are attacked by complement proteins. Complement binding produces an anaphylaxis‐like reaction and causes nanoparticles to be cleared from circulation by phagocytes. To defend nanoparticles, in article number 2107070, Jacob W. Myerson, Jacob S. Brenner, and co‐workers demonstrate how to conjugate nanoparticles to humans' natural complement inhibitor, Factor I, which defends the nanoparticle from complement attack, thus ameliorating all the above problems.